THE TRANSFORMATION OF 21ST CENTURY LEARNING ASSESSMENT IN COURSES OF CURRICULUM 2013 - Supriyono, Supriyono; Prabowo, Jumbuh (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
The research studied a teaching and learning process on assessment of  courses in curriculum 2013. An assessment is a process intended to figure out whether the process and the results of an activity program have been consistent with the predetermined goals or criteria. Therefore, it is necessary to comprehend how the transformation or change of assessment in 21st Century learning actually is. This assessment is done in an integrated manner with the teaching and learning process continuously. Here, the competence consists of three competence domains, namely (1) affect (attitude which deals with emotion), (2) psychomotor (having something to do with physical movement and use motor skill), and (3) cognitive domains (related to knowledge and intellectual ability development). The achivement of national education quality never be separated from the 8 national education standards, that are (1) standard of competence, (2) standard of content, (3) standar d of process, (4) standard of educator and education staff, (5) stnandard of facility and infrastructure, (6) management, (7) financing, and (8) educational assessment. The results showed that a teacher or educator should have ideally standar of teaching and learning process and aware to the teaching and learning goals.